2022
DOI: 10.1002/prep.202100220
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Environmental Assessment of Explosive Residues from the Detonation of Insensitive High Explosive Filled 155 mm Artillery Shell

Abstract: Insensitive High-Explosive (IHE) typically comprises up to five constituents including 2,4-dinitroanisole (DNAN), 3-nitro-1,2,4-triazol-5-one (NTO), and 1,3,5-trinitroperhydro-1,3,5-triazine (RDX), which are mixed in various ratios to achieve desired performance and increase insensitivity. Insensitive munitions, which are designed to detonate on command and not accidentally, are currently in use in military operations and training areas around the world. However, there is minimal literature available on the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…As a large mass endmember to the IMX‐104 mortar munitions, Persico et al. [31] performed CD on 155 mm projectiles filled with 11.2 kg of IMX‐104 and sampled residues deposited on sand; however, NTO was found to be relatively minor (71–762 mg/projectile) compared to DNAN (230–2630 mg/projectile), and no residual RDX was detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a large mass endmember to the IMX‐104 mortar munitions, Persico et al. [31] performed CD on 155 mm projectiles filled with 11.2 kg of IMX‐104 and sampled residues deposited on sand; however, NTO was found to be relatively minor (71–762 mg/projectile) compared to DNAN (230–2630 mg/projectile), and no residual RDX was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Walsh et al [3] also observed a scaling effect in Composition B residues from the live fire of 60 mm, 81 mm, and 120 mm mortar cartridges, although these munitions used different fuzes with differing booster charges. As a large mass endmember to the IMX-104 mortar munitions, Persico et al [31] performed CD on 155 mm projectiles filled with 11.2 kg of IMX-104 and sampled residues deposited on sand; however, NTO was found to be relatively minor (71-762 mg/projectile) compared to DNAN (230-2630 mg/projectile), and no residual RDX was detected.…”
Section: Insights Into Residue Phenomenonmentioning
confidence: 99%
“…37,38 However, because TNT has a low vapor pressure, it can be easily released into the atmosphere during the preparation or destruction of artillery shells, resulting in the contamination of water and soil. 39,40 Moreover, TNT is poisonous and causes skin irritation and harmful effects on the immune system. 41,42 In this regard, although TNT sensing with MOFs has been intensively investigated, studies reporting on the change in the characteristics of TNT using MOFs have been scarce despite the considerable difference in electron density between them.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 NTO with a theoretical detonation velocity of 8500 m s À1 exhibits energy comparable to 1,3,5-trinitro-1,3,5-triazacyclohexane (RDX), along with weak toxicity, simple preparation as well as low sensitivity, which has attracted more and more attention in the field of propellants and mixed explosives. [8][9][10] However, active hydrogen bonds in the molecular structure of NTO lead to strong acidity, and the corrosiveness to metals severely restricts the loading and application of ammunition. 11,12 Therefore, acid inhibition technology is generally regarded as an effective method to realize the broad development prospects of NTO.…”
Section: Introductionmentioning
confidence: 99%